CASE REPORT OF AUTOIMMUNE HEPATITIS AND CONCOMITANT PRIMARY BILIARY CHOLANGITIS (International Seven Journal of Multidisciplinary, 2025)
Autoimmune hepatitis with concomitant primary biliary cholangitis has rarely been reported. In this case, we describe a 57-year-old woman who had criteria for this diagnosis based on a liver biopsy that showed a mixed infiltrate of lymphocytes associated with interface hepatitis, rosettes, emperipolesis, plasma cells, and over 50% of the portal ducts did not have a central biliary duct. The treatment provided was Azathioprine, prednisone, and omeprazole, which led to a remarkable complete normalization of her liver enzymes after four weeks. This successful treatment outcome underscores the importance of early identification and treatment for improving long-term outcomes.